Evaluation of Physicochemical Properties of Agricultural Lands in Dand and Arghandab Districts, Kandahar Province - Obaid, Hikmatullah; Faiz, Mukhtar Ahmad; Ehsan, Qudratullah; Zaryal, Khalilullah (Journal of Natural Sciences – Kabul University, 2025)
This study was conducted in 2024 at the Afghanistan National Agricultural Sciences and Technology University, Kandahar, Afghanistan, with the objective of evaluating the physicochemical properties of agricultural soils in the Dand and Arghandab districts. A total of 60 soil samples were randomly collected from different agricultural lands within the two districts and analyzed in the laboratory. The results indicated that the average water holding capacity of the soils was 58.4 ± 3%, the pH was 8.4 ± 0.07, the electrical conductivity (EC) was 0.754 ± 0.33 dS/m, the organic carbon content was 0.79 ± 0.2%, the organic matter was 1.35 ± 0.4%, and the total nitrogen was 673 ± 61 kg/ha. Overall, the soils of Dand and Arghandab districts were classified as high in water holding capacity, alkaline in pH, non-saline in electrical conductivity, low in organic carbon, poor in organic matter, and low in total nitrogen.